Spontaneous mutation conferring the ability to catabolize mannopine in Agrobacterium tumefaciens - LaPointe, G; Nautiyal, C S; Chilton, W S; Farrand, S K; Dion, P (Journal of Bacteriology, 1992)
Two nopaline-type strains of Agrobacterium tumefaciens, C58 and T37, as well as strain A136, which is a Ti plasmid-cured derivative of strain C58, gave rise to spontaneous mutants that were able to grow on mannopine. The observation of mutagenesis with strain A136 demonstrated that the ability to acquire this new catabolic potential was independent of the presence of a Ti plasmid. The mutants were isolated after 4 weeks of incubation on minimal medium containing mannopine as the sole carbon source. They also utilized mannopinic acid, but not agropine or agropinic acid. In addition, the spontaneous mutant LM136, but not its parent strain A136, degraded many mannityl opine analogs. [(14)C]mannopine disappeared in the presence of LM136 cells which had been pregrown on opine or nonopine substrates. These results suggested that the catabolic system of this mutant was not subject to a stringent regulation. A clone conferring the ability to utilize mannopine on a recipient pseudomonad was selected from a genomic library from both the mutant LM136 and its parent strain. Only the LM136 clone was expressed in the parent Agrobacterium strain A136. Southern analysis showed that the genes for mannopine catabolism in the spontaneous mutants differed from the corresponding Ti plasmid-encoded genes of octopine-type or agropine-type Agrobacterium strains. Cells of LM136 utilized [(14)C]mannopine without generating detectable amounts of intracellular agropine. In contrast, a major fraction of the radioactivity recovered from cells of the octopine-type strain Ach5, after incubation on [14C]mannopine, was in the form of agropine.